Two-dimensional calculations of stratified turbulent flow in a pipe - Matveev, S.K.; Jaichibekov, N.Zh.; Shalabayeva, B.S.; Zhussupova, D. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In this paper, we consider the stratified turbulent flow of a two - phase medium in inclined pipes. Based on the new turbulence model [1], a program code for calculating two - dimensional flows for the study of two - phase stratified flows in pipes was developed, including taking into account the rough of the pipeline wall. The technique for calculating two - phase flows in extended pipelines is described. The problem of stationary stratified two - phase flow in a pipe of constant cross section in the case of turbulent regime is numerically solved. Calculations of the resistance of a rough pipe are carried out and the results on the influence of roughness on pipe resistance and velocity distribution are presented.